2014
DOI: 10.1002/anie.201404355
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Amination of Aryl Sulfides with Anilines

Abstract: A combination of a palladium-NHC catalyst and potassium hexamethyldisilazide enables the amination of aryl sulfides with anilines to afford a wide variety of diarylamines. The reaction conditions are versatile enough for the reaction of even bulky ortho-substituted aryl sulfides. This amination can be applied to the modular synthesis of N-aryl carbazoles from the corresponding ortho-bromothioanisoles. As aryl sulfoxides undergo extended Pummerer reactions to afford ortho-substituted aryl sulfides, the Pummerer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 102 publications
2
36
0
1
Order By: Relevance
“…In line with our interest in catalytic C−S bond transformations,,– we herein report that simple insertion of tert ‐butyl isocyanide into the C−S bonds of heteroaryl sulfides proceeded by means of a palladium catalyst to provide thioimidates (Scheme e). The resulting thioimidates could be easily converted into the corresponding thioesters by acidic hydrolysis.…”
Section: Methodssupporting
confidence: 56%
“…In line with our interest in catalytic C−S bond transformations,,– we herein report that simple insertion of tert ‐butyl isocyanide into the C−S bonds of heteroaryl sulfides proceeded by means of a palladium catalyst to provide thioimidates (Scheme e). The resulting thioimidates could be easily converted into the corresponding thioesters by acidic hydrolysis.…”
Section: Methodssupporting
confidence: 56%
“…Once again, NHC ligands were found to play a key role in the amination reaction of aryl sul des. 24 Treatment of methyl phenyl sul de (34) with p toluidine (35a) by means of IPr ligated Pd NHC precatalysts gave the corresponding aminated product 36a in good yields (Table 4, entries 2 6). Especially, SingaCycle A3 proved to be the optimal precatalyst, and nally, a 91% yield of 36a was isolated in the presence of KN(SiMe 3 ) 2 as base in dioxane at 100…”
Section: With Aminesmentioning
confidence: 99%
“…The development of new catalytic reactions of C–S bonds would be an important challenge, since C–S bonds are found widely in organic feedstocks, synthetic intermediates, and useful products. As a part of our recent research into catalytic C–S bond cleavage,11 we reported the first palladium‐catalyzed amination of aryl sulfides (Scheme ) 11c. A palladium–NHC (N‐heterocyclic carbene) precatalyst, SingaCycle‐A3, showed excellent reactivity for C–S bond cleavage.…”
Section: Introductionmentioning
confidence: 99%